A aprendizagem da Geometria do Táxi e suas relações com habilidades do pensamento computacional - Viana, Lucas Henrique (2025)
Taxicab Geometry (TG) constitutes an alternative approach to understanding and engaging with school geometry. Distinguished by its unique metric in contrast to traditional Euclidean Geometry, TG facilitates the representation of everyday situations and fosters interdisciplinarity with another fields. Similarly, Computational Thinking (CT) emerges as a theme that can be addressed transversally throughout the school curriculum, attracting the interest of educators and researchers from diverse fields. Given the opportunities offered by these two themes, especially their cross-curricular nature, it is necessary to conduct studies that deepen the exploration of the connections between them. Within this perspective, this study aims to analyze the relations between learning TG and developing CT skills. Research was conducted as a qualitative study case and applied to 14 high school students enrolled in an elective course at a full-time school in Campina Grande (Paraiba, Brazil). The fieldwork was organized into twelve moments: surveying student profiles; introducing TG concepts; associating TG with Pascal’s Triangle and combinatorial analysis; solving problems involving stops or detours; calculating distances within TG; using and adapting a game created by the researcher, the Geometric Uber; developing and sharing material with the school community. Data was collected through multiple sources, including video recordings, photos, personalized maps, challenges, CT test and forms. All data were analyzed using MaxQDA and interpreted through the lens of reflexive thematic analysis. Results indicated increased student motivation and engagement, the revisiting of geometric concepts and 16 relations between TG learning and the five CT skills: decomposition, pattern recognition, abstraction, algorithms and evaluation. Based on these relationships, it is expected that this study will contribute to the advancement of research on the transversality of Computational Thinking, specifically its connections with TG, in such a way that new practices and activities may be created focusing on develop one or more of its skills. Finally, research proposes directions to future work, such as producing and registering educational and conducting further studies to expand teaching and research horizons in CT across diverse educational contexts.